"Live High-Train Low" paradigm: Moving the debate forward - Brocherie, F.; Millet, G. P. (Exercise and Sport Sciences Reviews, 2018)
The recent article by Drs. Bejder and Nordsborg (http://doi.org/10.1249/JES.0000000000000144) on the weakness of scientific evidences supporting that the hypobaric or normobaric "live high-train low" (LHTL) method improves sport-specific exercise performance has the merit of recalling the importance of careful methodological design for future altitude-related research. Although we agree that double blinding, inclusion of a normoxic control group, implementation of a lead-in period, adequate sample size, and statistical power are paramount to minimize the potential biases (e.g., placebo or nocebo effect, training content or trainability influence), several comments would merit consideration.